A Short Note on : Basic Behavior of the Mount Gamalamas Eruption - Lilik Hendrajaya; Surono Surono; Gunawan Handayani (Jurnal Matematika & Sains, 1996)
Hypothesis that the tectonic force release through earthquake will trigger eruption of near by volcano when its magma pocket is full of magma, is put forward. It is mechanically reasonable due to the fact that both magma and the pocket are inside the earth crust which suffers compression stress resulted from the pushing force of oceanic crust in the subduction zone. Observation is conducted at Mount Gamalama in the island of Ternate west of the Halmahera Island, North Molluca. It is expected to have strong pushing force condition. The result shows that the triggering phenomenon is present. The other important results are the understanding of process to produce repeated volcanic eruptions and the knowledge of eruption mechanism.